DATA ON ADVANCED GLYCATION END-PRODUCTS CONCENTRATIONS AND HAEMODYNAMIC PARAMETERS FOLLOWING CAFFEINE AND NICOTINE CONSUMPTION IN NURSING STUDENTS - Deltsidou, Anna; Zarikas, Vasilios; Mastrogiannis, Dimos; Kapreli, Eleni; Bourdas, Dimitrios; Raftopoulos, Vasilios; Noula, Maria; Lykeridou, Katerina (Data in Brief, 2020)
This work presents data from a non-invasive interventional trial investigating the early effects of caffeine and nicotine on both the concentrations of advanced glycation end-products (AGEs) and haemodynamic parameters in 178 healthy nursing students aged between 18 and 40. These students were allocated into four groups (A, B, C and D) and the concentrations of AGEs as well as haemodynamic parameters were measured non-invasively using the AgeReader and the Finometer devices, respectively. The haemodynamic parameters that were measured included systolic blood pressure, diastolic blood pressure, mean arterial pressure, heart rate, inter-beat interval, stroke volume, cardiac output, ventricular ejection time, total peripheral resistance, ascending aorta impedance and total arterial compliance. According to our protocol, each beverage contained 100 mg of caffeine each cigarette contained 1.5 mg of nicotine. The present data reveal the combined effect of smoke and caffeine consumption to several hemodynamic parameters that may be related to the onset of elevated blood pressure during smoking and following caffeine consumption
Keywords: Advanced glycation end-products; haemodynamic effects; caffeine; smoking